Development and application of an amplified luminescent proximity homogeneous assay-linked immunosorbent assay for the accurate quantification of kidney injury molecule-1 - Fu, Yulin; Sun, Danqin; Qin, Yuan; Zheng, Tianyu; Zhou, Zixuan; Zhou, Xiumei; Zhao, Xueqin; Xu, Yan; Huang, Biao (Frontiers in Molecular Biosciences, 2024)
Kidney injury molecule-1 (Kim-1), a specific marker of kidney injury, is usually not expressed in normal kidneys or at very low levels but is highly expressed in injured renal tubular epithelial cells until the damaged cells recover completely. Therefore, we aimed to develop an efficient and highly sensitive assay to accurately quantify Kim-1 levels in human serum and urine. In this study, a novel immunoassay was developed and named amplified luminescent proximity homogeneous assay-linked immunosorbent assay (AlphaLISA). Anti-Kim-1 antibodies can be directly coupled to carboxyl-modified donor and acceptor beads for the rapid detection of Kim-1 by double-antibody sandwich method. Serum and urine samples for Kim-1 measurements were obtained from 129 patients with nephropathy and 17 healthy individuals. The linear range of Kim-1 detected by AlphaLISA was 3.83-5000 pg/mL, the coefficients of variation of intra-assay and inter-assay batches were 3.36%-4.71% and 5.61%-11.84%, respectively, and the recovery rate was 92.31%-99.58%. No cross reactions with neutrophil gelatinase-associated lipocalin, liver-type fatty acid binding protein, and matrix metalloproteinase-3 were observed. A good correlation (R 2 =0.9086) was found between the findings of Kim-1-TRFIA and Kim-AlphaLISA for the same set of samples. In clinical trials, both serum and urine Kim-1 levels were significantly higher in patients with nephropathy than in healthy individuals, especially in patients with acute kidney injury. Furthermore, serum Kim-1 was superior to urinary Kim-1 in distinguishing between patients with nephropathy and healthy individuals. The developed Kim-1-AlphaLISA is highly efficient, precise, and sensitive, and it is suitable for the rapid detection of patients with acute kidney injury.